Switchgrass and Prairie Cordgrass Response to Foliar- and Soil-Applied Herbicides. (December 2014) - Anderson, Eric K.; Hager, Aaron G.; Voigt, Thomas B.; Lee, D.K.
Abstract : Perennial grasses are expected to comprise a substantial portion of the lignocellulosic biomass to meet renewable energy mandates in the U.S. in the next decade. As many warm-season grasses are slow to establish from seed, plantings are often compromised by weed interference during the establishment year. Greenhouse experiments were conducted to determine the tolerance of switchgrass and prairie cordgrass to several herbicides applied PRE or POST (at four different growth stages). Preemergence atrazine at rates ≤ 1.684 kg ai ha −1 in switchgrass and quinclorac at rates ≤ 0.279 kg ai ha −1 in prairie cordgrass did not significantly reduce emergence, plant height, or biomass yield 8 wk after treatment. When treatments were applied at the two- to three-leaf stage, only atrazine (≤ 0.123 kg ai ha −1 ) did not reduce switchgrass fresh weight and only 2, 4-D ester (≤ 0.533 kg ae ha −1 ), nicosulfuron (0.018 kg ai ha −1 ), and quinclorac (0.140 kg ha −1 ) did not significantly reduce prairie cordgrass yield. Phytotoxic effects decreased for all herbicides with increasing growth stage at the time of treatment for both species. All evaluated herbicides were safe with respect to biomass yield on the respective grasses when applied at the latest growth stage (approximately five-leaf stage). These results show that viable PRE and POST herbicides are available for weed control during establishment of switchgrass and prairie cordgrass; however, all evaluated herbicides would likely reduce biomass yield in a mixture planting of both grasses.